DNA methylation links prenatal smoking exposure to later life health outcomes in offspring - Wiklund, Petri (Clin Epigenetics, 2019)
BACKGROUND: Maternal smoking during pregnancy is associated with adverse offspring health outcomes across their life course. We hypothesize that DNA methylation is a potential mediator of this relationship. METHODS: We examined the association of prenatal maternal smoking with offspring blood DNA methylation in 2821 individuals (age 16 to 48 years) from five prospective birth cohort studies and perform Mendelian randomization and mediation analyses to assess whether methylation markers have causal effects on disease outcomes in the offspring. RESULTS: We identify 69 differentially methylated CpGs in 36 genomic regions (P value < 1 × 10(−7)) associated with exposure to maternal smoking in adolescents and adults. Mendelian randomization analyses provided evidence for a causal role of four maternal smoking-related CpG sites on an increased risk of inflammatory bowel disease or schizophrenia. Further mediation analyses showed some evidence of cg25189904 in GNG12 gene mediating the effect of exposure to maternal smoking on schizophrenia-related outcomes. CONCLUSIONS: DNA methylation may represent a biological mechanism through which maternal smoking is associated with increased risk of psychiatric morbidity in the exposed offspring. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13148-019-0683-4) contains supplementary material, which is available to authorized users.